Youth mental health crisis: A translational view of the COVID-19 pandemic - Thorhildur Halldorsdottir (Neurobiology of Stress, 2025)
Mental health problems among children and adolescents have increased over the past two decades, a trend that was further exacerbated by the COVID-19 pandemic. To improve prevention and treatment strategies, developmentally informed and data-driven multidisciplinary approaches are urgently needed to clarify the mechanisms underlying youth vulnerability and resilience. Stress and trauma exposure are among the strongest predictors of youth mental health problems; however, most children and adolescents remain resilient despite such exposures. The widespread and heterogeneous challenges posed by the COVID-19 pandemic offer a unique opportunity to examine, at scale, who develops mental health problems under stress and who remains resilient. Integrating emerging findings on pandemic-related risk and protective factors with evidence from animal models can illuminate sensitive developmental periods of heightened susceptibility to environmental influence and biological embedding. This approach can identify when, how, and through what pathways mental health problems emerge, including gene–environment interactions and epigenetic mechanisms. Such knowledge will inform both behavioral and pharmacological interventions, pinpointing not only specific treatment targets but also the optimal timing for intervention to be the most effective.